Discriminating cosmological expansion models with third generation gravitational wave detectors - Souza, Josiel Mendonça Soares de (2019)
At the dawn of Gravitational Wave Astronomy, new avenues have been opened to test and constrain cosmological models. By simulating standard sirens detected by the third generation ground-based gravitational wave detector, Einstein Telescope, we show how we one can discriminate among different cosmological models. In this work, we use 10-year projected data of Einstein Telescope to compare the standard cosmological model (the Lambda CDM) with models using different phenomenological parametrizations of the equation of state for the dark energy.